(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article provides a comprehensive analysis of the problem of cognitive style as studied in foreign psychological research. Cognitive style is defined as a stable individual difference in the way people perceive, process, organize, and utilize information. The aim of the study is to examine the evolution of cognitive style theory, identify major classifications, and analyze its role in psychological, educational, and organizational contexts. The paper reviews classical and modern approaches, including field dependence–independence, analytic–intuitive styles, and integrative models of cognitive processing. The analysis demonstrates that cognitive styles significantly influence learning strategies, decision-making processes, problem-solving approaches, and interpersonal behavior.